PENGARUH PENGGUNAAN MEDIA VIDEO TERHADAP HASIL BELAJAR SISWA PADA KOMPETENSI DASAR PENGOPERASIAN MESIN BUBUT - Nugraha, Alfian Andy (Journal of Mechanical Engineering Learning, 2014)
This study aims to determine the improvement of student learning outcomes and determine the effect of the use of video media and to know how big influence on learning outcomes. This study used a quasi experimental design (Quasi Experimental Design) to design forms Nonequivalent Control Group Design. The population is the entire class XI student of SMK Muhammadiyah TP in Salatiga, whereas samples taken were students of class XI TP 3 the number of 37 students. Data collection using questionnaires or tests and questionnaires. T - test analysis results obtained tcount = 2.097 > table = 1.69, then the better the experimental group than in the control group. Student learning outcomes in the pre-test showed an average of 65.67 for the experimental group and the control was 68.43, while the learning outcomes of students in post-test shows the average experimental group was 79.83 and 74.71 for the control, then learning using video media can improve student learning outcomes. From the results of the regression analysis obtained 32,72% of student learning outcomes are influenced by the use of video media.